Comprehensive analysis of performance, physiological, and perceptual responses during an entire sprint cross-country skiing competition - Kjøsen Talsnes, R.; Berdal, T.; Brattebø, J.-M.; Seeberg, T.; Losnegard, T.; Kocbach, J.; Sandbakk, Ø. (European Journal of Applied Physiology, 2024)
Purpose To investigate performance, physiological, and perceptual responses of an entire sprint cross-country skiing competition in the skating style.